Practical Diets for Litopenaeus Vannamei (Boone, 1931): Working Towards Organic and/or All Plant Production Diets. - Davis, D. Allen; M. Samocha, Tzachi; A. Bullis, Robert; Patnaik, Susmita; L. Browdy, Craig; D. Stokes, Alvin; L. Atwood, Heidi (Avances en Nutrición Acuicola, 2019)
As shrimp prices become more competitive and the profit margins declining, producers are looking to high value markets for their products. Shrimp produced using organic or environmentally friendly production conditions have the potential to bring in higher prices through market differentiation. However, if one is to develop production schemes for such markets, one must also produce an organic feed or one that has minimal levels of marine proteins and oils. In previous research we developed a practical diet formulation without fish meal but containing marine fish oil. Since supplies of fish oil are also limited, this work concentrated on replacement of the marine oil source as well as the testing of an experimental organic diet. In the first experiment, fish oil in two of the diets was substituted by oil originating from commercially produced algae containing approximately 50% oil. These diets as well as a commercial feed were offered to juvenile Litopenaeus vannamei (Boone, 1931) over a 15 week growth trial. At the conclusion of the growth trial, survival, final weight, and feed conversion ratio (FCR) were not significantly different among treatments. In the second experiment, the diet previously tested using plant and algae oils was tested against a diet using only plant oils. To examine the potential of an organic diet, a practical diet using primarily organic ingredients was also tested. The three diets were tested in conjunction with a commercial control diet over a 12-week growth period. At the conclusion of this trial, shrimp reared on the organic diet and the diet without algae oil supplements were significantly smaller than those offered the commercial control. This result is presumably due to a lack of HUFA in the diets without algae oils high in DHA and AA. To further test the potential of a feed without fish meal, a commercial version of one of the test diets was produced at a feed mill and tested under pond production conditions. As this was only a demonstration, statistical differences cannot be determined but the feed did appear to produce acceptable results under commercial pond production conditions. Based on the results of these studies, it would appear that both fish meal and marine oil sources can be removed from shrimp feeds if suitable alternative sources of protein and lipids are provided to meet essential amino acid and fatty acid requirements of the shrimp. Although this study confirms the biological feasibility of fish meal and fish oil replacement at the densities tested, commercial application will require further analysis of relative costs and marketing benefits of these technologies.